Clemente Palma in the affection and malice of José de la Riva Agüero and Osma - Adriazola Silva, Juan Carlos (2020)
Many are the characters around Ricardo Palma who are closely linked to his existence and who will continue to relate to each other even after the death of the traditionist in 1919. In this opportunity, we will focus specifically on two of them: his eldest son, the writer and journalist Clemente Palma; and his loyal and devoted admirer, the great Peruvian polygrapher José de la Riva-Agüero y Osma. The firstis a member of the Modernist generation and the second, part of the generation of the Nineteenth Century or Arielista. This communication aims to reveal the details of that relationship and how long it lasted over time.